PEMBUATAN FILM BIOPLASTIK NANOKRISTAL SELULOSA PELEPAH NIPAH (Nypa Fruticans) YANG DIHASILKAN DARI PROSES SONIKASI-HIDROTERMAL DENGAN PENAMBAHAN PATI SAGU - Supran Hidayat Sihotang; Kasrawati (University of Bengkulu, 2024)
The manufacture of palm leaf frond (Nypa fruticans) nanocrystalline bioplastic films produced from a sonication-hydrothermal process with the addition of sago starch. This research aims to determine the characteristics of bioplastics made from cellulose nanocrystals with the addition of sago starch. Characterization uses tensile test methods, water absorption, FTIR, XRD, TGA, and biodegradability tests. The highest tensile strength results for bioplastics were shown in samples with a 20% NCC film variation, namely 11.996 MPa, elongation 1.66%, and Young's modulus 722.65 MPa. The best water absorption test is found in the 20% NCC variation, namely 24.35%. FTIR spectrum analysis shows the absorption of the C-O-C group at a wave number of 1096 cm-1 which identifies the presence of glycosidic bonds in cellulose nanocrystals. Peak 3428 indicates the presence of an O-H group and peak 2926 cm-1 indicates the presence of a C-H group. XRD analysis shows the degree of crystallinity of cellulose nanocrystals, namely 90%. The 15% NCC variation shows good heat stability around 335.71oC and the 20% NCC variation is 327.91%. The best biodegradability test was shown by samples with an NCC variation of 15%, namely 71.68%. The conclusion in this research is that the best sample variations are NCC variations of 20% and 15%.